The Effect of Vascular Cell Seeding on Platelet Deposition in an In Vitro Capillary Perfusion Model - Dekker, A; Poot, A; Beugeling, T; Bantjes, A; van Aken, W G (Thrombosis and Haemostasis, 1989)
In view of the reported beneficial effects of cell seeding on the performance of synthetic vascular grafts, we determined the deposition of 111Indium-labelled human platelets in polyethylene capillary tubes covered with human endothelial cells (HEC) or smooth muscle cells (SMC) using an in vitro perfusion model. Platelet deposition decreased with increasing vascular cell coverage and was virtually absent when the number of adherent vascular cells of both types exceeded 50,0001cm2. Platelet deposition increased with increasing she ar rate (300-900 s-1) only when surface coverage was less than 50,000 vascular cells/cm2.Deposition of Ca2+-ionophore A 23187-activated platelets in capillary tubes completely covered with SMC was significantly higher compared to capillaries covered with a similar number of HEC.When HEC-lined capillaries were treated with aspirin, only the deposition of activated platelets increased slightly, but significantly. This platelet reactivity was more evident when the endothelial lining was not confluent.These results demonstrate that, although seeding of HEC and SMC may both prevent the deposition of non-activated platelets to surfaces, non-aspirin-treated confluent HEC linings offer the best protection against deposition of activated platelets.
Keywords: Cell seeding; Platelet deposition; Flow conditions